Removal of dissolved organic carbon in the West Pacific hadal zones - Mengfan Chu; Rui Bao; Michael Strasser; Ken Ikehara; Yang Ding; Kejian Liu; Mingzhi Liu; Li Xu; Yonghong Wang; Piero Bellanova; Troy Rasbury; Martin Kölling; et al. (Nature Communications)
Abstract The deep oceans are environments of complex carbon dynamics that have the potential to significantly impact the global carbon cycle. However, the role of hadal zones, particularly hadal trenches (water depth > 6 km), in the oceanic dissolved organic carbon (DOC) cycle is not thoroughly investigated. Here we report distinct DOC signatures in the Japan Trench bottom water. We find that up to 34% ± 7% of the DOC in the trench bottom is removed during the northeastward transport of dissolved carbon along the trench axis. This DOC removal increases the overall DOC recalcitrance of the deep Pacific DOC pool, and is potentially enhanced by the earthquake-triggered physical and biogeochemical processes in the hadal trenches. Radiocarbon analysis on representative oceanic transects further reveals that the Pacific deep-water DOC undergoes distinct removal compared to those in the Atlantic and Indian Oceans along the thermohaline transport. Our findings highlight hadal trenches as previously unrecognized DOC sinks in the deep ocean system, with varying dynamics that warrant further investigation.